Validitas LKS berbasis problem solving bermuatan critical thinking skill pada materi alat optik dan pemanasan global fisika SMA/MA - Nadila Putri Bungsu; Yenni Darvina; Wahyuni Satria Dewi; Amali Putra (PILLAR OF PHYSICS EDUCATION, 2019)
The 21st century demands skills that can support human life. Human life is never separated from the various demands that require them to have quality resources so as to make a large contribution to their lives and the lives of the nation. One of the 21st century skills is the 4C skill, namely communication skills, critical thinking skills, collaboration skills and creativity skills. With these 4C skills, students are expected to be ready to face life's challenges and to have quality resources so they don't miss the flow of life and have good competitiveness. In LKS things that we can see from the 4C skills are critical thinking skills, for that in designing LKS we can further highlight them on critical thinking skills, while other 4C skills can be reviewed in the student learning process. However, in learning at SMA N 1 SUTERA 4C skills, especially critical thinking skills have not been fully applied, even though it is really needed. This research belongs to the type of R&D (Research and Development) contained in Sugyono's book. In this discussion we will only see the results of product validity.After product validation, 84.25% was obtained and is in the very valid category. This states that the worksheet can already be used in learning physics